1997
DOI: 10.1097/00005072-199707000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the Pathogenesis of Senile Plaques and Congophilic Angiopathy in Alzheimer Disease

Abstract: M a r c e l M . V e r b e e k , P ie t E ik e l e n b o o m , a n d R o b e r t M . W . d e W a a l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Furthermore, these data are in line with our previously proposed hypothesis that the pathogenesis of CAA and senile plaques is different, e.g. with respect to the involvement of Aβ‐associated proteins [41]. Finally, the exact role of sHsps in the deposition, aggregation or clearance of Aβ in AD brains needs further elucidation but may provide a target for interference with this disease.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, these data are in line with our previously proposed hypothesis that the pathogenesis of CAA and senile plaques is different, e.g. with respect to the involvement of Aβ‐associated proteins [41]. Finally, the exact role of sHsps in the deposition, aggregation or clearance of Aβ in AD brains needs further elucidation but may provide a target for interference with this disease.…”
Section: Discussionsupporting
confidence: 88%
“…Effects of Aβ on the vessel wall are particularly described for Aβ 1‐40 , whereas Aβ 1‐42 is mainly involved in senile plaque formation 14, 28. Because of the strong correlation between Aβ 1‐40 and Aβ 1‐42 plasma levels, we could not assess the individual effects of Aβ 1‐40 conditional on Aβ 1‐42 and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CAA-affected vessels, unlike senile plaques, contain significant Aβ40 in addition to Aβ42, 49 which is abundantly found in senile plaques. This specific pattern of Aβ40/42 deposition in CAA is reflected by decreased levels of both Aβ40 and Aβ42 peptides in CSF obtained from patients with CAA, diagnosed according to the Boston criteria, 50 a finding replicated by other groups.…”
Section: Biomarkers Advances and Mechanistic Insightsmentioning
confidence: 99%